2021
DOI: 10.1111/eos.12846
|View full text |Cite
|
Sign up to set email alerts
|

A secret of salivary secretions: Multimodal effect of saliva in sensory perception of food

Abstract: Saliva plays multifunctional roles in oral cavity. Even though its importance for the maintenance of oral health has long been established, the role of saliva in food perception has attracted increasing attention in recent years. We encourage researchers to discover the peculiarity of this biological fluid and aim to combine the data concerning all aspects of the saliva influence on the sensory perception of food. This review presents saliva as a unique material, which modulates food perception due to constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 233 publications
0
8
0
1
Order By: Relevance
“…As known, the incorporation of saliva into a bolus while chewing transforms the initial value of moisture content in solid or semisolid foods to prepare a ready-to-swallow bolus in the mouth [ 37 ]. A gravimetrical analysis of saliva content in the bolus formed from the PGs revealed that saliva uptake varied between 22.6 and 29.1 wt% in pectin hydrogels ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, the incorporation of saliva into a bolus while chewing transforms the initial value of moisture content in solid or semisolid foods to prepare a ready-to-swallow bolus in the mouth [ 37 ]. A gravimetrical analysis of saliva content in the bolus formed from the PGs revealed that saliva uptake varied between 22.6 and 29.1 wt% in pectin hydrogels ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the compositions of the PGs were similar, serum release appeared to be a critical initial characteristic of pectin hydrogels that could affect saliva secretion during oral processing and subsequent saliva uptake into the bolus. Saliva not only hydrates the bolus but also lubricates it by lowering friction due to its watery character and the presence of salivary mucins, thereby making swallowing the bolus safe [ 37 , 40 ]. Therefore, PG5, with its low serum release (0.49%), needed more saliva incorporation to enhance lubrication than PG1 (serum release 0.66%).…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in concentration of mineral salts (including inorganic salts contained in the artificial saliva) could be responsible for the decrease in the salting-out effect. However, the effect of saliva on the release of aroma compounds is complex and sometimes contradictory [ 26 ]. For example, it has been reported that the dilution effect of saliva decreased the viscosity of a product and contributed to a more intense perception [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those who perceived high avor intensity also perceived a greater saliva secretion when chewing gum freestyle. Although salivary characteristics such as ow rate, composition, and buffer capacity modulate avor perception through different mechanisms, the avor stimulus itself can also regulate salivary ow and composition [24,39]. In addition, high inter-individual and intra-individual variability exists in masticatory laterality, avor perception, and salivary ow because many factors alter these behaviors and sensations [23].…”
Section: Discussionmentioning
confidence: 99%